Improving the Way We See: Adaptive Optics Based Optical Microscopy for Deep-Tissue Imaging - Sahu, Pranoy; Mazumder, Nirmal (Frontiers in Physics, 2021)
With the recent developments in optical imaging tools and techniques, scientists are now able to image deeper regions of the tissue with greater resolution and accuracy. However, light scattering while imaging deeper regions of a biological tissue remains a fundamental issue. Presence of lipids, proteins and nucleic acids in the tissue makes it inhomogeneous for a given wavelength of light. Two-photon fluorescence (TPF) microscopy supplemented with improved invasive optical tools allows functional imaging in awake behaving mammals in an unprecedented manner. Similarly, improved optical methods conjugated with previously existing scanning laser ophthalmoscopy (SLO) has paved diffraction-limited retinal imaging. With the evolving technology, scientists are now able to resolve biological structures and function at the sub-cellular level. Wavefront correcting methods like adaptive optics (AO) has been implemented in correcting tissue or optical-based distortions, shaping the excitation beam in 3D-holography to target multiple neurons. And more recently, AO-based SLO is implemented for eye imaging both in research and clinical settings. In this review, we discuss some of the recent improvements in TPF microscopy with the application of AO for wavefront corrections and its recent application in brain imaging as well as ophthalmoscopy.